Institutions in Transition: Changing Trends in Marriage - P.M. Kumar, Suresh (RESEARCH REVIEW International Journal of Multidisciplinary, 2023)
Marriage is a wedded relationship between members of opposite sexes, except otherwise sanctioned by law of the land, to unite together for a durable relationship of responsibility and need gratification. It is an institutional arrangement, compliance of which is mandatory to obtain social approval. Traditionally marriage amounted to a union of families characterized by larger involvement of family and kin and reciprocal relationships built between each other and consequent enlargement of the family circle, rather than that of two individuals. In the caste-ridden traditional Indian society, caste and communities functioned as a boundary wall limiting the expansion of choices. Contrary to this are the sparingly few still relevant self-selection marriages or love marriages which are hailed for cutting across diversities and developing deeper mutual understanding that is at the core of relationships, an alarming number of them end up in failure very soon. Modern marriages are business deals involving investments and matching of mutual gains. The modus operandi stands out hosting in lavish hotels and halls with huge spending on food, clothes, ornaments, and arrangements. The matching process itself is complex involving a host of factors such as age, education, appearance and beauty, wealth, profession, family status, the value of dowry, and astrological compatibility. This paper seeks to bring out the transition from home-based to hall-based marriage practices and accompanying changes marking the shift from traditional to modern marriages. It also tries to expose the role of compatibility matching as an intricate process involving innumerable factors in which age assumes the role of a major bargaining factor. Qualitative analysis involving experiential surveys and focus group discussions with key informants was adopted for the collection of data.